Movement behavior in adults with sickle cell disease compared to healthy adults: a cross-sectional study - Aaron A. Heeren; Eduard J. van Beers; Bart J. Biemond; Myrthe J. van Dijk; Erfan Nur; Charlotte F.J. van Tuijn; Merel A. Timmer (PLoS ONE, 2026)
Background Sickle cell disease (SCD) is one of the most common monogenic disorders in the world. Patients with SCD have chronic hemolytic anemia and experience episodic pain due to vaso-occlusion resulting in, amongst other, musculoskeletal and cardiopulmonary complications. We hypothesize that adults with SCD are less physically active, but limited information is available on the movement behavior of adults with SCD. In the current study, we aimed to evaluate movement behavior in patients with SCD as compared to healthy controls. Methods Movement behavior of patients with SCD (≥16 years) was prospectively collected in two University Medical Centers in the Netherlands. Movement behavior was measured for seven consecutive days with an accelerometer (Activ8), distinguishing between lying/non-wear, sitting, walking, running, and biking. Time spent on activities was compared between patients with SCD and healthy adults with a migration background and between HbSS/HbSβ 0 and HbSC/Hbβ + using the Man-Whitney U test. To adjust for multiple testing, season, sex, and age, a linear regression for each activity was performed. Results Data of 30 patients with SCD during steady state (median age 32.1 (IQR 25−47)) and 57 healthy adults (median age 37 (30−50)) were analyzed. Patients with SCD walked 0.68 (CI −1.22 to −0.14) h/day less than healthy adults. No differences were identified for other postures and activities. Every point increase in hemoglobin level was associated with 0.26 (CI 0.01 to 0.52) h/day increase in walking duration. Conclusion and key findings Patients with SCD appear to be less physically active compared to healthy adults, which is mainly reflected by reduced walking time (around 3500 steps less a day), highlighting the need for tailored physical activity support.